Transformation to electronic purchasing: an empirical investigation - Mansour Naser Alraja; Maryam Ali Said Kashoob (Universitas Ahmad Dahlan, 2019)
The main objective of this study is to determine the factors influence consumers in Oman to switch from in-store to electronic purchasing. Therefore, four constructs (perceived ease of use (PEU), perceived usefulness (PU), facilitating conditions (FC), and social influence (SI)) have been employed in this study which are adopted through the integration between UTUAT and TAM models. The respondent in this study were students from Sultan Qaboos University and Dhofar University, 537 cases have been analysed. Exploratory, confirmatory, and structural equation modelling techniques have been employed in this research using SPSS 25, AMOS 25 software.The study revealed that (PU), (FC), and (SI) have a positive and significant influence on the consumers’ behavioural intention in Oman to switch into electronic purchasing. While, the findings demonstrated that there is no significant effect by (PEU) on the consumers’ behavioural intention to transform from traditional to electronic purchasing.The study provides business and consumers, a good interpretation about the factors influence the transformation to e-purchasing. In addition, this paper encourages companies to shift to interaction e-purchasing portals which help businesses to target different marketplace inside and outside of country to increase sell ratio to sustain their business. However, up to the researchers’ knowledge this study considered to be among the first studies which provide another clearer view of e-purchasing in Oman by incorporating selected factors from two different theories. i.e. incorporating two factors related to the use of technology with other two variables about the required technical resources, and the social effect on individuals to use new technology, thereby being unique and original.